The Construction of Justice from the Perspective of Social Contract Legal Philosophy: A Comparative Study of Hobbes, Locke, and Rousseau in the Context of Indonesian Law - Suhartoyo Suhartoyo (International Journal Labs, 2025)
This study analyzes the concept of justice from the perspective of the Social Contract Theory according to Thomas Hobbes, John Locke, and Jean-Jacques Rousseau. These three philosophers have different views on social contracts and justice. Hobbes emphasized the importance of the state in protecting individuals from brutal natural conditions; Locke emphasized the importance of individual natural rights and the role of the state in protecting those rights; while Rousseau emphasized the importance of the general will of society and the role of the state in upholding that general will. By using juridical-philosophical and comparative analysis methods, this study shows that justice from the perspective of the Social Contract Theory is the highest value for the state to uphold. Therefore, the state has an important role in realizing justice for citizens in Indonesia by increasing political awareness and active participation of citizens, ensuring transparency and accountability in government and political parties, protecting citizens' rights, and promoting popular sovereignty. Thus, justice can be realized for all citizens.